Implementasi Media Susat Suling untuk Mendukung Pemahaman Konsep Hubungan Sudut Pusat dan Sudut Keliling Lingkaran - Maulana, Ahmad Riyan (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to describe the implementation of the Susat Suling media based on GeoGebra in supporting students’ understanding of the relationship between central angles and inscribed angles in circles. A descriptive quantitative method with a one-shot case study design was employed. The subjects of this study were 35 students from class XI IPS 1 at MAN 1 Lamongan. The instruments used included validation sheets and learning outcome tests. Expert validation results indicated that the Susat Suling media achieved a feasibility score of 87.7%, which falls into the 'Highly Feasible' category. Following its implementation in the classroom, data showed that 82.9% of students scored ≥70 on the post-test. These results suggest that the media effectively facilitated students’ understanding of the central and inscribed angle concepts in a more concrete and interactive manner. Thus, Susat Suling can serve as an innovative alternative for visual-based mathematics instruction